PERILAKU ANTISOSIAL REMAJA PEMAIN GAME ONLINE DI DESA SEBAGU KECAMATAN TELUK KERAMAT KABUPATEN SAMBAS - Zulfikri Zulfikri; Amrazi Zakso; Supriadi Supriadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractTechnological advances can be felt both directly and indirectly, marked by the development of the spread of internet networks that cover almost all social strata. In the last few years, electronic games or what we usually call online games have experienced very rapid development. The main objective of this study is to explain the implications of using gamesonline against antisocial behavior among adolescents in Sebagu Village, Teluk Keramat District, Sambas Regency. This study uses descriptive qualitative research methods and data collection techniques used are observation, interviews, and documentation study. informants in this study were adolescents in general who play online games .The results of research and discussion that have been conducted by researchers, concluded that the behavior of using online games by adolescents causes adolescents to have anti-social behavior, the behavior of adolescents playing online games until late at night anddisturbing the general order. Online games are generally used for entertainment but what happens is online games are played excessively, used as a place to escape from the realities of life so that what happens is addictiononline game.Keywords : Adolescents, Anti-Social, Online Game